2018 International Conference on Indoor Positioning and Indoor Navigation (IPIN) 2018
DOI: 10.1109/ipin.2018.8533772
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Bayesian Filters for RSS-Based Device-Free Localization and Tracking

Abstract: Received signal strength (RSS)-based device-free localization applications utilize the communication between wireless devices for locating people within the monitored area. The technology is based on the fact that humans cause changes in properties of the wireless channel which is observed in the RSS, enabling localization of people without requiring them to carry any sensor, tag or device. Typically this inverse problem is solved using an empirical model that relates the RSS to location of the sensors and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…the heading and its location. Kaltiokallio et al [72] compared the relative performance of PF and EKF. The study concluded that for indoor positioning based on RSS, they are largely similar with the exception of the computational overhead, which favours the EKF.…”
Section: Methods Of Fusionmentioning
confidence: 99%
“…the heading and its location. Kaltiokallio et al [72] compared the relative performance of PF and EKF. The study concluded that for indoor positioning based on RSS, they are largely similar with the exception of the computational overhead, which favours the EKF.…”
Section: Methods Of Fusionmentioning
confidence: 99%
“…Some researchers used RSS-based algorithms for localization, e.g. Kaltiokallio et al used RSS in a recursive particle filter to achieve a high localization accuracy, but it also required a high number of reference tags [22]. Hsiao et al used the "Real Time Location System" with multiple reference tags to enhance the localization accuracy of a person equipped with RFID tags [23].…”
Section: Related Workmentioning
confidence: 99%
“…In the first, the person is located using an imaging approach [9], [10] and a Kalman filter (KF) is used for tracking [11], [12]. In the second, a propagation model together with a nonlinear Bayesian filter such as a particle filter (PF) [13], [14], [15] or an extended Kalman filter (EKF) [16] is used to track the kinematic state of the target. The considered problem can be solved more accurately using a nonlinear Bayesian filter, however, these filters are known to suffer from divergence issues if the modeling errors are significant [17, p.128].…”
Section: Introductionmentioning
confidence: 99%
“…The work is motivated by deriving the posterior Cramér-Rao bound (PCRB) for the RSS-based DFLT problem and evaluating two estimators with respect to the bound. The used RSS-based DFLT estimators are: an EKF-based method [16] and a modified radio tomographic imaging (RTI) method [12]. The analysis clearly shows that RTI is lower bounded by the pixel size of the discretized image and this bound is significantly higher than the PCRB.…”
Section: Introductionmentioning
confidence: 99%